The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/17460441.2019.1659242
|View full text |Cite
|
Sign up to set email alerts
|

PROTACs– a game-changing technology

Abstract: Introduction: Proteolysistargeting chimeras (PROTACs) have emerged as a new modality with the potential to revolutionize drug discovery. PROTACs are heterobifunctional molecules comprising of a ligand targeting a protein of interest, a ligand targeting an E3 ligase and a connecting linker. The aim is instead of inhibiting the target to induce its proteasomal degradation. Areas covered: PROTACs, due to their bifunctional design, possess properties that differentiate them from classical inhibitors. A structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 92 publications
1
109
0
1
Order By: Relevance
“…PROTACs are an exciting new modality of heterobifunctional molecules aiming to degrade the protein of interest instead of inhibiting it. 25 , 26 In 2019, Gray et al 27 reported the development of a cereblon-based degrader molecule library targeting KRASG12C and bearing acrylamide warheads. Although the lead PROTAC ( Fig.…”
Section: Recent Development Of Covalent Inhibitorsmentioning
confidence: 99%
“…PROTACs are an exciting new modality of heterobifunctional molecules aiming to degrade the protein of interest instead of inhibiting it. 25 , 26 In 2019, Gray et al 27 reported the development of a cereblon-based degrader molecule library targeting KRASG12C and bearing acrylamide warheads. Although the lead PROTAC ( Fig.…”
Section: Recent Development Of Covalent Inhibitorsmentioning
confidence: 99%
“…Galantamine acts simultaneously as an AChE inhibitor and allosteric modulator of nicotinic receptors, increasing the affinity for ACh [114][115][116][117][118][119][120][121][122][123][124][125][126][127][128]. Research in progress on novel AD drugs has covered different disciplines and been focused on further development of AChE inhibitors, beta-secretase 1 (BACE-1) inhibitors, serotonin 5-HT4 receptor inhibitors and PROTAC (PROteolysis Targeting Chimeras) compounds, among other approaches [129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146]. Rivastigmine is regarded to react with the serine residue of the ES present in AChE and BChE (as shown in Scheme 3), whereas donepezil can act in both CAS and PAS of AChE.…”
Section: Reversible Inhibition Of Ache: a Tool For Treatment Of Admentioning
confidence: 99%
“…As part of our ongoing interest in proteolysis targeting chimeras (PROTACs), we aimed to produce libraries centered around the glutarimide pharmacophore addressing the E3 ligase Cereblon using multicomponent reactions (MCR) . For this, we went back to a report of the use of glutamine (Gln) in the Ugi reaction (U‐5C‐4CR), yielding highly substituted glutarimide derivatives (Figure A) .…”
Section: Figurementioning
confidence: 99%